Transaksi Jual Beli Pre-Order Merchandise K-Pop Pada Grup Order Wonderland Dalam Perspektif Fiqih Muamalah - Irfilia Azzahra Putri; Muhammad Zuhirsyan; Muslim Marpaung (DPPM Universitas Pelita Bangsa, 2026)
This study aims to analyze the practice of pre-order sales of K-pop merchandise in the Wonderland Group Order from the perspective of Islamic commercial jurisprudence (fiqh muamalah). The researcher employed a qualitative descriptive method, collecting data through interviews with group administrators, consumers, as well as experts in Islamic jurisprudence and Islamic economics. The results show that the pre-order transaction system implemented in this group aligns with the principles of Islamic law, particularly the salam contract. In this contract, the specifications of the goods are clearly agreed upon, and payment is made either partially or fully in advance, with the goods delivered at a predetermined future time. Although the transactions are carried out digitally, the essential elements of ijab (offer) and qabul (acceptance) are fulfilled, making the transaction valid according to Islamic law.